PUBLIC TRANSPOTATION SERVICE INNOVATION BUY THE SERVICE PROGRAM TRANS BANYUMAS IN BANYUMAS REGENCY (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2023)
Public service is a measure of how well the government has implemented programs in the public eye. The performance of the government can be judged by the community based on whether the services offered are or are not a service and how the government develops new solutions to regional problems. One of the districts in the Southwest and part of Central Java province is Banyumas. Because transportation is one of the public services that can support the continuity of economic activity in a region, economic activity will never stand alone without the help of the government. To reduce congestion and be able to reduce the volume of existing vehicles in Banyumas Regency, the Banyumas Regency government (Pemkab) launched an innovative public transportation service, namely the Trans Banyumas Bus, the purpose of the Trans Banyumas Bus itself was launched by none other than to facilitate transportation services in Banyumas Regency. The purpose of this study is to explain the service innovation that is bus Trans Banyumas. In this study used the literature study method and using secondary data as a reference. As a result, this study can explain the related impact of the Trans Banyumas Bus, which is to minimize spending money on fuel, reduce pollution, and reduce congestion.